ЖАСЛАР САНАСЫНДА ӘДЕП-ИКРАМ ҲӘМ ҲУҚЫҚЫЙ ТӘРБИЯНЫ ҚӘЛИПЛЕСТИРИЎДЕ КӨРКЕМ ӘДЕБИЯТТЫҢ ОРНЫ - Алламбергенов, Е.К. (FAN va JAMIYAT, 2017)
The article is devoted to the study of issues of law education and exprossing the ideas of struggle against law violation in the works of fiction the years of Independence on the example of the works of the famous poets I.Yusupov, M.Jumanazarova and G.Dauletova. In the conclusion it is emphasized that literary work plays a great aesthetic role as a means of upbringing in moral and law education and development of law culture in the youth’s consciousness.